Theorizing ICT and Society in the Brazilian Context: a Multilevel, Pluralistic and Remixable Framework - Marlei Pozzebon; Eduardo Henrique Diniz (BAR: Brazilian Administration Review, 2012)
In this paper we present a multilevel and pluralistic conceptual framework that is particularly useful for Brazilian researchers investigating information and communication technology (ICT) based social changes from a community/societal level of analysis. The framework is influenced by three theoretical perspectives: social shaping of technology, structurationist view of technology and contextualism. It integrates four main concepts – relevant social groups, interpretive frames, negotiation and technology-in-practice – organized in terms of three dimensions – context, process and content. The framework, already applied to 12 different research projects led by Brazilian scholars during the last four years, is seen as a work in permanent transformation and open to reuse, revision, remix and constant revalidation.